2013
DOI: 10.1038/nature12639
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between autophagy and ciliogenesis

Abstract: SummaryNutrient deprivation is a stimulus shared by both autophagy and the formation of primary cilia. The recently discovered role of primary cilia in nutrient sensing and signaling motivated us to explore the possible functional interactions between this signaling hub and autophagy. Here we show that part of the molecular machinery involved in ciliogenesis also participates in the early steps of the autophagic process. Signaling from the cilia, such as that from the Hedgehog pathway, induces autophagy by act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
457
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 365 publications
(492 citation statements)
references
References 31 publications
22
457
1
4
Order By: Relevance
“…It is possible that forming autophagosomes (phagophores) have different motility than fully formed ones and changes in the fraction of phagophores with age could account for the observed differences. However, in previous studies with the LC3‐tandem reporter, we have not observed colocalization of the moving dual color vesicles with phagophore markers such as Atg5 (Bejarano et al., 2014; Pampliega et al., 2013), and consequently, we think that the resolution of our approach is not enough to detect these early forming membranes that contaminate our measurements. Whether differences in the cargo carried by autophagosomes with age could determine their different speed deserves future study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is possible that forming autophagosomes (phagophores) have different motility than fully formed ones and changes in the fraction of phagophores with age could account for the observed differences. However, in previous studies with the LC3‐tandem reporter, we have not observed colocalization of the moving dual color vesicles with phagophore markers such as Atg5 (Bejarano et al., 2014; Pampliega et al., 2013), and consequently, we think that the resolution of our approach is not enough to detect these early forming membranes that contaminate our measurements. Whether differences in the cargo carried by autophagosomes with age could determine their different speed deserves future study.…”
Section: Discussionmentioning
confidence: 93%
“…To separately analyze autophagosome biogenesis, we next compared changes in the levels of LC3‐II at 2 and 4 hrs after inhibitor treatment (since degradation is already blocked, an increase in LC3‐II can only originate from de novo synthesis of autophagosomes; Pampliega et al., 2013). These studies revealed significantly lower rates of autophagosome formation under basal conditions in primary fibroblasts from old mice (Figure 1e,f).…”
Section: Resultsmentioning
confidence: 99%
“…9 This allows the autophagic process to control the length of the PC in response to the environmental changes. The degradation of IFT20 occurs predominantly via basal autophagy, 7 and that of OFD1 is observed early during serum starvation-induced autophagy. 9 OFD1 is encoded by the gene involved in the X-linked ciliopathy, the OFD1.…”
Section: Autophagy and Ciliummentioning
confidence: 99%
“…5 Recent studies have shown that signals emanating from ciliated structures control the formation of autophagosomes. 7 A role for autophagy in ciliogenesis and control of cilia length has also been demonstrated. [7][8][9] The aim of this review is to present the recent findings that uncover the interplay between cilia and autophagy and to discuss their potential impact on cell homeostasis and oncilia-related disease.…”
Section: Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation